Ok. You have to cross multiply:
2(x-1) = x+1
2x-2 = x+1
x= 3
2007-04-17 12:50:47
·
answer #1
·
answered by John Smith 2
·
0⤊
1⤋
(x+1) / ( x-1) can also be written as a fraction with (x+1) on the top, and x-1 on the bottom. Rewrite that portion of the equation as a fraction, and make the 2 a fraction as well. Any number can be converted to a fraction by putting it over a 1, since fraction and division are the same thing, and any number divided by one ( or placed over a one ) is itself.
Now that both sides are fractions, solving for the value of X will be much easier.
If 2/1 = x+1/x-1, then you can cross multiply. While I cannot give you the exact reasoning for this, it is common mathematical procedure.
let * = multiply
therefore, 1 * x+1 = 2 * x-1
anything times 1 is itself, so the first half of the equation is simply x+1.
for the second half, when multiplying a number by a binomial ( x-1, for example ) you distribute that number. In other words, multiply the 2 by both the x and the -1.
We now get 2x-2 for the second half of the equation, giving us
x+1 = 2x-2 as our full equation.
We now get all the X terms to one side, and all the numerical terms on the other.
subtract one from both sides. we get X = 2X-3 ( negative 2 minus one is negative 3 )
subtract 2X from both sides. we get -X = -3 ( x minus two x's is negative x )
an equation in which both sides are negative can be switched so that all sides are positive, thus giving us the answer:
X =3
I hope that helped you not only get the answer, but understand how to solve other similar problems :D
2007-04-17 19:59:22
·
answer #2
·
answered by Brendan 2
·
1⤊
0⤋
Think of 2 and being 2/1: now just cross multiply to get the whole solution process going.
2007-04-17 19:51:31
·
answer #3
·
answered by bruinfan 7
·
0⤊
1⤋
Multiply both sides by (x-1) and you get
2(x-1)=x+1
2x-2=x+1
x-2=1
x=3
2007-04-17 19:52:32
·
answer #4
·
answered by Joemaroon 2
·
0⤊
1⤋
2=(x+1)/(x-1) Multiply both sides by (x-1)
2(x-1)=x+1 factor
2x-1=x+1 subtract 1 from both sides
2x-2=x subtract x from each side
x-2=0 add 2 to each side
x=2
2007-04-17 19:54:56
·
answer #5
·
answered by Justina 3
·
0⤊
1⤋
2 = (x + 1)/(x - 1)
==> 2(x - 1) = x + 1
==> 2x - 2 = x + 1
==> x - 2 = 1
==> x = 3
Like that. :)
2007-04-17 19:51:03
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋